2018
DOI: 10.1177/1356336x18816997
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy support, motivational climate, enjoyment and perceived competence in physical education: Impact of a hybrid teaching games for understanding/sport education unit

Abstract: The purpose of the study was to investigate the impact of a hybrid teaching games for understanding (TGfU) and sport education (SE) physical education unit on autonomy support, perceived motivational climate, enjoyment and perceived competence, in comparison to a unit delivered via a traditional direct instruction model. A crossover design was utilized. Participants were 55 students divided into two groups. One group experienced a hybrid TGfU/SE unit first, followed by a unit of direct instruction. A second gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 56 publications
(99 reference statements)
8
52
1
4
Order By: Relevance
“…Yet, no improvements were obtained in autonomous motivation, in relatedness satisfaction, and in intention to be physically active. In the other study conducted by Gil-Arias et al [32], significant improvements were observed in the students' perceptions of autonomy support from PE teachers in competence, satisfaction, and in enjoyment, when students received the hybrid SE/TGfU teaching unit. Therefore, due both to the limitation of studies, as well as the identification of some discrepancies in the findings, more studies which analyze the effects of the hybridization of these two models on a wide range of SDT-related variables, are required.…”
Section: Effects Of the Se Model And/or Tgfu Model On Sdt-related Varmentioning
confidence: 70%
See 4 more Smart Citations
“…Yet, no improvements were obtained in autonomous motivation, in relatedness satisfaction, and in intention to be physically active. In the other study conducted by Gil-Arias et al [32], significant improvements were observed in the students' perceptions of autonomy support from PE teachers in competence, satisfaction, and in enjoyment, when students received the hybrid SE/TGfU teaching unit. Therefore, due both to the limitation of studies, as well as the identification of some discrepancies in the findings, more studies which analyze the effects of the hybridization of these two models on a wide range of SDT-related variables, are required.…”
Section: Effects Of the Se Model And/or Tgfu Model On Sdt-related Varmentioning
confidence: 70%
“…To date, only two previous intervention studies have examined the effects of hybrid SE/TGfU teaching units in PE lessons on some SDT-related variables [32,33], and none of them have examined if less amotivated students could benefit more from this type of intervention. To fill this gap, this study aimed to examine the extent to which a hybrid SE/TGfU volleyball teaching unit was equally effective on a set of SDT-related variables according to students' initial motivation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations